2009
DOI: 10.1017/s0033291709006102
|View full text |Cite
|
Sign up to set email alerts
|

Is the antidepressive effect of second-generation antidepressants a myth?

Abstract: Two recent meta-analyses on second-generation antidepressants versus placebo in mild to moderate forms of major depression, based on data on all randomized clinical trials using the Hamilton Depression Scale (HAMD) submitted to FDA, have shown an effect size of y0.30 in favour of antidepressants in the acute therapy of major depression. The clinical significance of an effect size at this level was found to be so poor that these meta-analyses have subscribed to the myth of an exclusively placebo-like effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 41 publications
(79 reference statements)
0
46
0
Order By: Relevance
“…Table 4). These findings are likely to reflect a combination of the following: (i) HAM-D 6 captures the core symptoms of depression more specifically and is unbiased than the HAM-D 17 (which also taps into the side effects of many psychopharmacological agents, that is, nausea, sexual dysfunction, unintended weight gain, and sexual dysfunction) [47], (ii) HAM-D 6 is likely to be associated with lower placebo response rates than HAM-D 17 [68], (iii) many antidepressant therapies are more clinically effective than previously thought (and indicated by the HAM-D 17 ) [69]. …”
Section: Discussionmentioning
confidence: 99%
“…Table 4). These findings are likely to reflect a combination of the following: (i) HAM-D 6 captures the core symptoms of depression more specifically and is unbiased than the HAM-D 17 (which also taps into the side effects of many psychopharmacological agents, that is, nausea, sexual dysfunction, unintended weight gain, and sexual dysfunction) [47], (ii) HAM-D 6 is likely to be associated with lower placebo response rates than HAM-D 17 [68], (iii) many antidepressant therapies are more clinically effective than previously thought (and indicated by the HAM-D 17 ) [69]. …”
Section: Discussionmentioning
confidence: 99%
“…A review of the first controlled clinical trials in outpatients with major depression using zimeldine against amitriptyline demonstrated that amitriptyline was superior on non-core depressive symptoms, such as the sleep factor of the HAM-D, while no difference between the two drugs was seen concerning the HAM-D core symptoms of depression, such as depressed mood, guilt, work and interests, psychic anxiety, psychomotor retardation, and general somatic symptoms [42]. When evaluating the specific antidepressive effect, therefore, these core items (HAM-D 6 ) are to be used as the outcome measure and when using this scale the effect size is 0.40 or higher when SSRIs are compared to placebo [43]. …”
Section: Struggle To Identify a Mode-specific Effect Of Second-generamentioning
confidence: 99%
“…A number of other commentators, e.g. (Bech, 2009;Broich, 2009;Hegerl and Mergl, 2010;Khan and Khan, 2008;Mathew and Charney, 2009;McAllisterWilliams, 2008a;Moller, 2008;Nutt and Malizia, 2008;Parker, 2009;Turner and Rosenthal, 2008) have also criticized the Kirsch et al (2008) paper. The main arguments advanced by one or more of these commentators include:…”
Section: Further Remarks On Antidepressant Trialsmentioning
confidence: 99%